2015
DOI: 10.15517/am.v26i1.16921
|View full text |Cite
|
Sign up to set email alerts
|

Productividad de híbridos varietales de maíz de grano amarillo para valles altos de México.

Abstract: Productividad de híbridos varietales de maíz de grano amarillo para valles altos de México. El objetivo de este trabajo fue evaluar la productividad de híbridos varietales no convencionales de grano amarillo con respecto a las variedades progenitoras.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 5 publications
1
0
0
6
Order By: Relevance
“…The observed values for green forage were higher than the regional average of 47.8 t ha -1 (SIAP, 2014), and although there were no significant differences in dry forage, all treatments exceeded that reported by Salazar et al (2007) who obtained 23.6 t ha -1 with 160 t ha -1 of cattle manure. In the crude protein (PC) variable there were no statistically significant differences between treatments, and the values obtained were similar to the highest values reported by Tadeo-Robledo et al (2012) but lower than the national average reported by Nuñez (2006) of 10.3%. The decrease in crude protein content could be the result of the loss of leaf biomass coupled with a higher proportion of stem in the total biomass, which are deficient in crude protein content (Tariq et al, 2011).…”
Section: Resultssupporting
confidence: 78%
“…The observed values for green forage were higher than the regional average of 47.8 t ha -1 (SIAP, 2014), and although there were no significant differences in dry forage, all treatments exceeded that reported by Salazar et al (2007) who obtained 23.6 t ha -1 with 160 t ha -1 of cattle manure. In the crude protein (PC) variable there were no statistically significant differences between treatments, and the values obtained were similar to the highest values reported by Tadeo-Robledo et al (2012) but lower than the national average reported by Nuñez (2006) of 10.3%. The decrease in crude protein content could be the result of the loss of leaf biomass coupled with a higher proportion of stem in the total biomass, which are deficient in crude protein content (Tariq et al, 2011).…”
Section: Resultssupporting
confidence: 78%
“…En los mercados a futuro se considera que el precio internacional del maíz se mantendrá elevado y probablemente se incrementará; ante esta situación, la opción es producir maíz amarillo en México, para lo cual se requieren variedades mejoradas. El Programa de Mejoramiento Genético de Maíz del Valle de México ha propuesto como alternativa ofrecer materiales precoces con alto potencial productivo para promover el uso de semillas mejoradas entre los productores, dado su escaso empleo en condiciones de ambientes restrictivos y periodo corto libre de heladas, como ocurre en Valles Altos (2200 a 2600 msnm), para posibilitar el uso de semillas de grano amarillo en siembras muy tardías (Espinosa et al, 2010;2011;Espinosa-Calderón et al, 2013;Tadeo-Robledo et al, 2015); ésto permitiría que los agricultores incrementen la producción de grano.…”
unclassified
“…Para atender la demanda de semillas de maíz amarillo en el Estado de México la investigación pública ofrece variedades de polinización libre muy precoces, tolerantes al acame y con rendimientos aceptables, como son V-54 A, V-55 A y Oro Puma (Espinosa et al, 2010;2011;Tadeo-Robledo et al, 2015); más recientemente, se desarrolló el híbrido varietal HV 60 A (Tadeo et al, 2012a;2012b;Tadeo-Robledo et al, 2015). Si bien, las primeras variedades son una buena opción, se requieren materiales con mayor rendimiento y precocidad similar, como es el caso del híbrido varietal HV 60 A.…”
unclassified
See 1 more Smart Citation
“…Este maíz es usado principalmente para las actividades pecuaria e industrial. Es urgente elevar la producción de este tipo de grano, por lo que se requiere desarrollar nuevas variedades mejoradas públicas con ventajas (López-López et al, 2021;Luna et al, 2012;Martínez-Yáñez et al, 2017;Tadeo-Robledo et al, 2015).…”
unclassified